EFEKTIVITAS PROGRAM PENGEMBANGAN BP3K SEBAGAI MODEL CENTER OF EXCELENCE (CoE) DALAM PENINGKATAN KINERJA PENYULUH DI KECAMATAN BATANGHARI KABUPATEN LAMPUNG TIMUR - Fitriansyah Bakti Praja; Sumaryo Gitosaputro; Indah Listiana (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to know: the level of extensions performance before and after BP3K development program as CoE model, the effectiveness of BP3K development progam as CoE model in rising of extensions’ performances, and the relating factors to extensions performance of BP3K as CoE model in Batanghari Subdistrict of East Lampung Regency.  This research was conducted in 14 villages as the patronage regions in Batanghari Subdistrict from September until October 2013.  The samples were 11 agricultural extension workers and 88 patronage farmers chosen by proportional random sampling from two most active farmer groups.  The research data was analyzed by descriptive qualitative method and rank spearman analysis.  The result showed that the increasing level of extensions’ performances in BP3K of Batanghari Subdistrict before and after CoE program were increasing in arranging elucidation program, increasing in excellent agribusiness productivity in its own region, and up to now the extensions have been applying cyber extensions for helping the extensions activity. The effectiveness of CoE program in raising the extensions performance in BP3K of Batanghari Subdistrict was effective enough. The factors that significant with extensions performance were extension experiences, extension incomes, and formal education. Key words: CoE program, effectiveness, extension, farmer, performance